(untitled) (Research, Society and Development, 2022)
endemic in developing countries, including Brazil. This study aims to trace the epidemiological profilehelminthiasesases in schoolchildren in the Administrative District of Guamá. For this, 576 school-age children were randomly selected, aged between 5 and 14 years, students from the municipal public school system belonging to the Administrative District of Guamá. Data were obtained through a form with environmental and socioeconomic issues of the sample population. The analysis of the results showed that 50.35% were female and 49.65% were male, 59.5% were between 5 and 9 years old, 89.75% were studying elementary school, 69.27 % live in their own house, 62.15% of which are masonry, with 65.62% presenting from 01 to 04 rooms, the monthly family income is composed mostly, 67.02%, of up to 01 minimum wage. The findings allow us to conclude that despite the advances in public health policies for the school public, it is still necessary to move forward to minimize the data that point to geohelminthiases as a public health problem and, therefore, generate quality of life for the population.